PARTISIPASI POLITIK PEMILIH PEMULA DALAM BINGKAI JEJARING SOSIAL DI MEDIA SOSIAL - Loina L. K. Perangin-angin; Munawaroh Zainal (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
The purpose of this research to identify the social networking of early voters in the social media and its influence toward political participation. Using qualitative approach, the data is primarily collected through focus group discussion and in-depth interview with 63 college students chosen purposively in 3 big cities; Bandung, Jakarta, and Surabaya. Research results show that social media is massively used by the early voters for interacting and communicating because it needs no physical preparation and revelation of their original personality. The network is easily accessed, both on campus and at home, which sustains higher intensity in using social media. While networking socially, the early voters only interact and communicate with old acquaints, thus the networking does not aim for developing a new network. Their participation in politics is considered low, have less understanding about politics, and have not participated yet, both online and offline. Social media has become their primary source of political news and information for discussing with family and peers face-to-face. Discussion result becomes a consideration for their political decision making. The contribution of this research is to give perspectives on political participation of novice voters in social media in order to motivate social media users to become politically literate.